Population pharmacokinetics and pharmacodynamics of bivalirudin in young healthy Chinese volunteers - Zhang, Dong-mei (Nature Publishing Group, 2012)
AIM: To investigate the population pharmacokinetics (PK) and pharmacodynamics (PD) of bivalirudin, a synthetic bivalent direct thrombin inhibitor, in young healthy Chinese subjects. METHODS: Thirty-six young healthy volunteers were randomly assigned into 4 groups received bivalirudin 0.5 mg/kg, 0.75 mg/kg, and 1.05 mg/kg intravenous bolus, 0.75 mg/kg intravenous bolus followed by 1.75 mg/kg intravenous infusion per hour for 4 h. Blood samples were collected to measure bivalirudin plasma concentration and activated clotting time (ACT). Population PK-PD analysis was performed using the nonlinear mixed-effects model software NONMEM. The final models were validated with bootstrap and prediction-corrected visual predictive check (pcVPC) approaches. RESULTS: The final PK model was a two-compartment model without covariates. The typical PK population values of clearance (CL), apparent distribution volume of the central-compartment (V(1)), inter-compartmental clearance (Q) and apparent distribution volume of the peripheral compartment (V(2)) were 0.323 L·h(-1)·kg(-1), 0.086 L/kg, 0.0957 L·h(-1)·kg(-1), and 0.0554 L/kg, respectively. The inter-individual variabilities of these parameters were 14.8%, 24.2%, fixed to 0% and 15.6%, respectively. The final PK-PD model was a sigmoid E(max) model without the Hill coefficient. In this model, a covariate, red blood cell count (RBC(*)), had a significant effect on the EC(50) value. The typical PD population values of maximum effect (E(max)), EC(50), baseline ACT value (E(0)) and the coefficient of RBC(*) on EC(50) were 318 s, 2.44 mg/L, 134 s and 1.70, respectively. The inter-individual variabilities of E(max), EC(50), and E(0) were 6.80%, 46.4%, and 4.10%, respectively. CONCLUSION: Population PK-PD models of bivalirudin in healthy young Chinese subjects have been developed, which may provide a reference for future use of bivalirudin in China.